Keefektifan Metode Cooperative Script Berbantuan Media YouTube dalam Pembelajaran Menyimak Teks Biografi Kelas X - Maharani, Astri; Muhtarom, Imam; Sugiarti, Dewi Herlina (Universitas Muhammadiyah Surabaya, 2025)
The lack of learner involvement in the learning routine is caused by the use of inappropriate teaching and learning strategies, so it is easy to divert their interest and attention. The purpose of this research is to explain the efficacy of the cooperative script technique assisted by YouTube videos in learning activities for listening to biographies of class X students of SMK Bhinneka Karawang. This research applies a pseudo-trial technique with two samples X MPLB 1 and X MPLB 2. The results of hypothesis analysis are 0.000 < 0.05 which shows a significant difference between the control and trial classes. In addition, the trial class received a higher mean score of 81.875 compared to the control class which only achieved a mean score of 61.406.